MEASURING TAX COMPLIANCE: A HOLISTIC PERSPECTIVE ON TECHNOLOGY, BEHAVIOR, AND SPIRITUAL INTELLIGENCE - Orlando Yudistira; Rolyana Ferinia (Jurnal Ekonomi, 2023)
The background to the research problem is the low level of compliance in paying taxes from taxpayers. Therefore, the aim of this research is to analyze and understand the relationship between tax compliance and taxpayer behavior, understanding technology in paying taxes, and individual spiritual intelligence. The data collection technique used a questionnaire which was distributed directly to RT 010, 05, 04. The method used by researchers was a quantitative method with primary data processed from 108 respondents who were in modern park housing. The data analysis technique used in this research is Structural Equation Modeling (SEM) and analysis using SmartPLS. The results of the research, 1). There is a significant influence between understanding technology and compliance in paying taxes. 2). There is a significant influence between taxpayer behavior on the spiritual intelligence of taxpayers. 3). There is a significant influence between spiritual intelligence on compliance in paying taxes; 4). There is a significant influence between tax behavior on compliance in paying taxes through understanding technology; 5). There is no significant influence between Taxpayer behavior on compliance in paying taxes through spiritual intelligence. The originality of this research is that tax behavior greatly influences the use of tax technology, emphasizing the need for collaboration and education of tax officers and taxpayers in the early stages of digital taxation